2004
DOI: 10.1242/dev.01044
|View full text |Cite
|
Sign up to set email alerts
|

Development of definitive endoderm from embryonic stem cells in culture

Abstract: brachyury locus, we demonstrate that endoderm develops from a brachyury + population that also displays mesoderm potential. Transplantation of cells generated from activininduced brachyury + cells to the kidney capsule of recipient mice resulted in the development of endoderm-derived structures. These findings demonstrate that ES cells can generate endoderm in culture and, as such, establish this differentiation system as a unique murine model for studying the development and specification of this germ layer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

43
643
4
6

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 773 publications
(696 citation statements)
references
References 81 publications
43
643
4
6
Order By: Relevance
“…In these embryological contexts, our data showed that differentiation of endoderm or mesendoderm can be actively directed by exposing hEBs to serum and activin. Consistent with our study, a recent study using mouse ESCs [24] reported the positive effect of serum and activin on the differentiation of definitive endoderm. A more recent study using hESCs [35] also demonstrated that, under two-dimensional differentiation conditions, a population enriched with definitive endoderm can be generated by treatment with activin A at a low serum concentration (0.5%).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In these embryological contexts, our data showed that differentiation of endoderm or mesendoderm can be actively directed by exposing hEBs to serum and activin. Consistent with our study, a recent study using mouse ESCs [24] reported the positive effect of serum and activin on the differentiation of definitive endoderm. A more recent study using hESCs [35] also demonstrated that, under two-dimensional differentiation conditions, a population enriched with definitive endoderm can be generated by treatment with activin A at a low serum concentration (0.5%).…”
Section: Discussionsupporting
confidence: 93%
“…1a, when hEBs were treated with serum for 4 days and further differentiated in serum-free conditions for 6 days (S4/SF6), the expression of the genes encoding forkhead box protein A2 (FOXA2) and SRY-box containing gene 17 (SOX17) was significantly increased compared with control cultures (SF10). We also observed that the serum treatment markedly upregulated the expression of the mix1 homeobox-like 1 gene (MIXL1), a primitive streak marker, and T [human homologue of the mouse T (brachyury)], which is known to be expressed in mesendoderm [24] (Fig. 1a).…”
Section: Differentiation Of Hescs Into Endodermmentioning
confidence: 82%
“…We observed mRNA within 2-3 days for nestin (an early neural ectoderm marker) and brachyury (Brachy, an early mesoderm marker), whereas β-H1 globin (β-globin, a mesoderm marker) and α-fetoprotein (α-FP, an endoderm marker) mRNAs accumulated later (days 5-6). These patterns of expression are as previously reported for multilineage differentiation following LIF withdrawal [8,9,32,[38][39][40][41].…”
Section: Progesterone Receptor Gene Is Expressed Early During Differesupporting
confidence: 87%
“…The recent report of a technique for efficient generation of definitive endoderm from ES cells by culture in lower concentrations of serum and Activin A [7][8][9] has been an important advance for subsequent production of hepatocyte-like cells. We have found that induction of definitive endoderm from ES cells was a necessary step for subsequent hepatic differentiation in vitro.…”
Section: Protocols Have Been Developed To Differentiate and Enrich Vamentioning
confidence: 99%